DNA Aneuploidy in Ulcerative Colitis and in Colorectal Carcinoma – A Comparative Study - Roger Stenling; Bernt O. Jonsson; Richard Palmqvist; Jörgen N. Rutegård (Analytical Cellular Pathology)
DNA aneuploidy is of interest as an additive marker for carcinoma risk in ulcerative colitis. It is known that colorectal carcinomas often are aneuploid with DNA indices centered around a median value of 1.5, corresponding to triploidy, and that adenomas, if aneuploid, have DNA indices closer to 2.0, the tetraploid region. In a colonoscopic surveillance programme, colorectal mucosal biopsies from 104 patients with ulcerative colitis were examined by flow cytometry, and the DNA indices determined and compared with findings of cellular dysplasia. In 17 patients, DNA aneuploidy was diagnosed, with DNA indices ranging from 1.2 to 2.0, median 1.9. Three patients with high grade dysplasia all had DNA indices within the triploid region. These results were compared with the DNA indices from a group of 49 patients with non‐colitis‐associated aneuploid colorectal carcinomas, in which the levels ranged from 1.1 to 2.0 with a median value of 1.5. Accordingly, the DNA index in the colitis patients with aneuploidy was more often within the tetraploid region. These results, obtained in patients with ulcerative colitis, indicate a possible precancerous progress from diploidy over tetraploidy to triploidy also in patients with long‐standing ulcerative colitis. In addition, the results speak in favour of a connection between DNA indices in the triploid region and more profound premalignant alterations.